Growing seasons - Splear, Elsie Lee, 1906-; Stark, Ken (New York : G.P. Putnam's Sons, 2000)
Born into an Illinois farm family in 1906, Elsie Lee Splear describes how she, her parents, and her sisters lived in the early years of the twentieth century and how the changing seasons shaped their existence.
Wilson's Children.
School Library Journal starred.
Booklist.
4.6
3-6
Keywords: Splear, Elsie Lee, -- 1906- -- Juvenile literature; Splear, Elsie Lee, -- 1906-; Splear, Elsie Lee, -- 1906-; Farm life -- Illinois -- Juvenile literature; Farmers -- Illinois -- Biography -- Juvenile literature; Farm life -- Illinois; Farmers; Women -- Biography; Farm life -- Illinois; Farmers -- Biography; Women -- Biography; Farmers; Women -- Biography; Farm life; Illinois -- Biography -- Juvenile literature